Efficacy of two Phlebiopsis gigantea formulations in preventing Heterobasidion irregulare colonization of red pine stumps in eastern Canada - Dumas, Michael; Laflamme, Gaston (Phytoprotection, 2013)
Heterobasidion irregulare is the scientific name for the North American fungal species that was previously known as H. annosum (P-type) and Fomes annosus. In eastern Canada, the pathogen is found mainly in red pine plantations in southern Ontario and Quebec, where it causes tree mortality. There is no registered control method currently available for this disease in Canada. Phlebiopsis gigantea is a saprophytic basidiomycete successfully used and registered as a biological control agent in several European countries. In order to register a control product in Canada, its efficacy must be demonstrated under field conditions. Trials were performed with two Canadian isolates of P. gigantea in four red pine plantations in Ontario. The mean diameters of treated stumps ranged from 29 to 35 cm. After 2 mo, all 238 stumps treated were free of disease, while 12% of the 120 untreated stumps were colonized by the pathogen. The two formulations without P. gigantea did not prevent the colonization of the stumps by either P. gigantea or H. irregulare. These results show that the two Canadian isolates of P. gigantea can prevent colonization of red pine stumps by H. irregulare and provide support for the registration of P. gigantea as a biocontrol agent in eastern Canada.